ANALYSIS OF STUDENT DIFFICULTIES IN IPAS LEARNING AND PRACTICUM AT SDN 001 TANJUNGPINANG TIMUR - Andini, Nabila (Jurnal PTK dan Pendidikan, 2024)
Making science lesson plans in elementary school and practicum guides are needed to plan systematic learning in accordance with the material being taught so that learning objectives can be achieved and learning can be understood by students. In addition, to facilitate the delivery of a series of materials This research uses descriptive qualitative research with the subject, namely the V C class teacher of SD Negeri 001 Tanjungpinang Timur, the research was conducted using interview data collection techniques which were carried out on November 21, 2023. The interview process was assisted by question instruments, stationery and audio and visual recording devices. This research is intended and intended so that we can find out what problems are behind student understanding, the difficulty of making lesson plans and also the difficulty of determining appropriate media and practicum modules that can be easily understood, especially at SD Negeri 001 Tanjungpinang Timur.